MANFAAT EKONOMI DAN NON EKONOMI KOPERASI GUNUNG MADU (KGM) DI PT GUNUNG MADU PLANTATIONS (PT GMP) KABUPATEN LAMPUNG TENGAH - Amanda Putra Seta; Dyah Aring Hepiana Lestari; Suriaty Situmorang (Lampung University, 2016)
This study aims to analyze the economic benefits received by members of KGM, the contribution of cooperation economic benefits on household income of KGM members, and non-economic benefits (level of satisfaction) of the KGM members. This research was conducted in KGM, PT GMP, Central Lampung Regency. The total samples are 75 members of KGM. Data analysis method that used is the economic benefits of cooperative analysis, analysis of household income cooperative members, and analysis of the level of satisfaction of member cooperatives using the Customer Satisfaction Index (CSI) analysis. The results showed that the direct economic benefits derived by KGM members each year, was on average of Rp1,689,921.00, while the indirect economic benefits by KGM Members, each year, was on average of Rp9,565,067.00. Total economic benefits of KGM, contributing to income amounted to14.28% of members. Level of satisfaction of the members of KGM to KGM is 70.8 %, which means that members of the KGM feel satisfied with the performance of the services provided by the employee of KGM. Key words: Economic Benefit, Members of KGM, Non Economic Benefit